Identification of dna-HPV In adolescente and Young Women with no Intercourse - Eleutério, Renata Mirian N; Oliveira, Marco Aurélio P; Jacyntho, Claudia Márcia A; Eleutério Jr., José; Freitas, Josele R (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: the human papillomavirus (HPV) virus is an extremely prevalent in the world. Currently there are around 200 types identified, about 45 of which affect the anogenital area. Although the high prevalence of HPV infection among sexually active adolescents is known, few studies have succeeded in demonstrating the presence of the virus among girls before sexual intercourse. Objective: to assess the prevalence of human papillomavirus (HPV) in adolescents and young women prior to coitarche assisted at an outpatient gynecological unit. Methods: this study included 50 adolescents assisted at the gynecology unit in University Hospital Pedro Ernesto (HUPE), State University of Rio de Janeiro. The patients were below 20 years old, who reported no sexual intercourse and with intact hymen on physical examination by a gynecologist with broad experience, from January 2007 to January 2009. The material for study was collected from vulvar vestibule for detection of HPV-DNA by Hybrid Capture second generation (hC2). Results: in the 50 patients tested for HPV-DNA age ranged from 11 to 20 years old (mean: 15.88 + 2.04) and all of them denied coitus and had intact hymen. The hC2 was positive in three cases (6%). In two cases non-high risk HPV was detected and in one case high-risk HPV was identified. After 6 months, a second test for HPV-DNA was negative in two out of three patients. The third one was not tested. Conclusion: HPV infection can occur before the first sexual intercourse and even in situations where there is no genital contact.